Entrepreneurial experiences, competencies, and skills among selected indigenous farmers of highland vegetables in Bauko, Mountain Province - Alzate, Marby Karylle Ayson (College of Home Economics, University of the Philippines Diliman, 2020)
Throughout history, farmers have consistently been recognized as a vital sector of society, requiring substantial support and protection from the government, civil society organizations, and other recognized partners. Farmers are acclaimed as the main drivers towards food security by facilitating the affordability and accessibility of food in the market to be put on the table of every family in the country. However, consistent with the change of time, farmers have aspired to go beyond the cultivation of the soil and become agricultural traders and entrepreneurs. In some sort, farmers have challenged themselves and endeavored learning financial literacy, business plan preparation, and different marketing methods. In this study, the potential of the indigenous farmers from Bauko Mountain Province to become entrepreneurs was examined. The study described their capacity to manage their own business operation, their existing entrepreneurial skills, and their trading technique to market goods. The weaknesses and factors that hinder the farmers’ entrepreneurial ability were also investigated. A mixed method research design was employed for data collection. A quantitative method was used to initially determine the personal entrepreneurial competencies and limitations of the respondents. The information obtained in this section was used as a tool to appreciate the natural capabilities of the respondents. Meanwhile, a qualitative method was used to study the entrepreneurial experiences the farmer entrepreneurs encountered before, during, and after the planting and harvesting season. Meanwhile, a qualitative method was also used to study the business management skills of the farmers. A video and phone call interview and a selfadministered questionnaire were used to gather the data. The data were analyzed through descriptive statistics and narrative analysis.